Northern Crossings Translation, Circulation and the Literary Semi-periphery - Edfeldt, Chatarina (Cosmopolitan-Vernacular Dynamics in World Literatures, 2022)
This open access book uses Swedish literature and the Swedish publishing field as recurring examples todescribe and analyse the role of the literary semi-peripheral position in world literature from various perspectives and on meso, micro and macro levels, using both quantitative and qualitative methods. This includes the role of translation in the semi-periphery and the conditions under which literature travels to and from that position. The focus is not on Sweden, as such, but rather on the semi-peripheral transitional space as exemplified by the Swedish case. Consisting of three co-written chapters, this study sheds light on what might be called the semi-peripheral condition or the semi-periphery as an area of transition. As part of the Cosmopolitan and Vernacular Dynamics in World Literatures series, it makes continuous use of the concepts of 'cosmopolitan' and 'vernacular' - or rather, the processual terms, cosmopolitanization and vernacularization - which provide an overall structure to the analysis of literature and literary phenomena. In this way, the authors show that the semi-periphery is an ideal point of departure to further the understanding of world literature, because it is a place where the cosmopolitan (the literary universal) and the vernacular (the rootedness in a particular culture or place) interact in ways that have not yet been thoroughly explored. The open access edition of this book is available under a CC BY-NC-ND 3.0 licence on www.bloomsburycollections.com. Open access was funded by Riksbankens Jubileumsfond.